Segurança e saúde do trabalho em condomínios residenciais: plano de ação e emergência - Fantinato, Valéria Cristine (2014)
The implementation of the new Code of the Fire Department of Paraná comes into force in 2012 and aims mainly to prevention, with requirements covering various areas of coexistence even considered as low-risk, such as condominiums, which with larger became Condos club, thereby increasing the permanence of residents and their guests within these areas and the need for more and more service providers and employees. Aiming to identify the risks of condominiums in relation to the environments, activities, people and their attitude to emergencies, the study is based on legislation involving the subject of Health and Safety. Applying the methodology of research by questionnaires to the shareholders and liquidators of 4 (four) different sized condos, to identify the knowledge regarding the risks and condominiums, the result aims to relate these environments, activities and risks for modeling a plan action and direct emergency actions to care for possible occurrences within a residential condominium, covering everything from small domestic accidents as major accidents, protecting the tenants, their heritage and especially employees, direct or third party contractors.